2000
DOI: 10.1258/1357633001935914
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire for the assessment of patients' impressions of the risks and benefits of home telecare

Abstract: Home telecare is a promising method of improving access to care for rural and urban populations. It requires, however, that patients accept the installation and use of equipment in their home. How patients perceive home telecare may influence its acceptability and diffusion. We developed a questionnaire to assess patients' impressions of the risks and benefits of home telecare. A preliminary 20-item questionnaire was developed and tested on 32 subjects. It proved to be of acceptable reliability (Cronbach's alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(115 citation statements)
references
References 22 publications
4
108
0
3
Order By: Relevance
“…The final version of the instrument used for this study showed a high reliability (Cronbach's alpha of 0.8) and evidence of validity with respect to perceptions of telehomecare. 15 The items address the effect of telehomecare on quality of and access to health care, the issues of time and money (including time saving for the patient and/or the nurse, reduction of costs for the patient and/or for the health care agencies), and factors related to the conduct of a virtual visit (including ease of equipment use, equal acceptability of "virtual" and real visit, protection of privacy and confidentiality, lack of physical contact, reduced sense of intimacy, patient's ability to explain medical problems in a virtual visit). Finally, the general perception of the concept of telemedicine in home care is also addressed, including the augmentation versus substitution of standard home care as the future role of telemedicine in home care.…”
Section: Methodsmentioning
confidence: 99%
“…The final version of the instrument used for this study showed a high reliability (Cronbach's alpha of 0.8) and evidence of validity with respect to perceptions of telehomecare. 15 The items address the effect of telehomecare on quality of and access to health care, the issues of time and money (including time saving for the patient and/or the nurse, reduction of costs for the patient and/or for the health care agencies), and factors related to the conduct of a virtual visit (including ease of equipment use, equal acceptability of "virtual" and real visit, protection of privacy and confidentiality, lack of physical contact, reduced sense of intimacy, patient's ability to explain medical problems in a virtual visit). Finally, the general perception of the concept of telemedicine in home care is also addressed, including the augmentation versus substitution of standard home care as the future role of telemedicine in home care.…”
Section: Methodsmentioning
confidence: 99%
“…Yet some of these dimensions of patient satisfaction are not often examined and seldom examined collectively. Contributing dimensions of patient satisfaction with telemedicine are often only studied in relationship to instrument development [35,36]. However even among instruments developed specifically for evaluating telemedicine satisfaction, there is a lack of consistency in the dimensions of satisfaction examined.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Questions were adapted from other telemedicine studies and evaluated seven areas of satisfaction 37,38 : willingness to pay, ease of comprehension of SMS, comfort with the monitoring duration and the time of day when the SMS was sent, impact of the system on patient privacy and ease of contact with the pharmacist, and usefulness of advice generated. Patients could also provide qualitative feedback.…”
Section: Data Collectionmentioning
confidence: 99%